Surface Hopping Dynamics with Correlated Single-Reference Methods: 9H-Adenine as a Case Study - Plasser, Felix; Crespo-Otero, Rachel; Pederzoli, Marek; Pittner, Jiri; Lischka, Hans; Barbatti, Mario (Journal of chemical theory and computation, 2014)
Surface hopping dynamics methods using the coupled cluster to approximated second order (CC2), the algebraic diagrammatic construction scheme to second order (ADC(2)), and the time-dependent density functional theory (TDDFT) were developed and implemented into the program system Newton-X. These procedures are especially well-suited to simulate nonadiabatic processes involving various excited states of the same multiplicity and the dynamics in the first excited state toward an energetic minimum or up to the region where a crossing with the ground state is found. 9H-adenine in the gas phase was selected as the test case. The results showed that dynamics with ADC(2) is very stable, whereas CC2 dynamics fails within 100 fs, because of numerical instabilities present in the case of quasi-degenerate excited states. ADC(2) dynamics correctly predicts the ultrafast character of the deactivation process. It predicts that C2-puckered conical intersections should be the preferential pathway for internal conversion for low-energy excitation. C6-puckered conical intersection also contributes appreciably to internal conversion, becoming as important as C2-puckered for high-energy excitations. In any case, H-elimination plays only a minor role. TDDFT based on a long-range corrected functional fails to predict the ultrafast deactivation. In the comparison with several other methods previously used for dynamics simulations of adenine, ADC(2) has the best performance, providing the most consistent results so far.